Do N-of-1 Trials Need IRB Review?. (July 2016) - Cen, Ruiqi; Hussain, Azad; Pak, Kirk J.; Mitchell, Geoffrey; Nikles, Jane; Gaudreau, Stephanie; Bazzano, Lydia A.; Breault, Joseph L.
There is no standard policy regarding the regulatory or institutional approval of N-of-1 trials in the United States. The objective of this study was to examine whether institutional review boards (IRBs) accredited by the Association for the Accreditation of Human Research Protection Programs (AAHRPP) consider N-of-1 trials as meeting the definition of human subjects research (45CFR46.102) and requiring IRB approval. A questionnaire was distributed via email to 170 AAHRPP-accredited IRBs in the United States. Responses were analyzed using statistical and qualitative methods. Nineteen of 59 respondents reported viewing N-of-1 trials as research. Twelve respondents reported having a policy regarding N-of-1 trials, and in all cases, such policies did not consider N-of-1 trials as meeting the definition of research. This topic deserves wider examination in the IRB literature and community to inform policies and guidance as N-of-1 trials become more common in the pursuit of personalized, precision medicine.